The retardation of polyacrylamide by ammonium chloride in high-salinity and high-temperature conditions: molecular analysis - Amir, Z. (Springer, 2020)
Salinity effects on retardation efficiency of ammonium chloride (NH4Cl) on the polyacrylamide (PAM) that influences the gelation time of PAM-based polymer gel are an interesting phenomenon. This paper presents a concise investigation by quantifying molecular interaction of PAM with NH4Cl in high-salinity and high-temperature conditions. This study quantified the ionic bonding of carboxylate group of PAM with ammonium ion of NH4Cl using zeta-potential, hydrodynamic radius, and hydrolysis degree. Experimental results show that in the absence of NaCl and NH4Cl, the overall magnitude absolute values of zeta-potential, hydrodynamic radius, and hydrolysis degree of PAM show a significant increase. The absolute value of zeta-potential reduces with the concentration of NH4Cl as retarder. On the other hand, the hydrodynamic radius and hydrolysis degree tend to increaseÂ with the concentration of NH4Cl, even in high salinity. The retardation process is also fairly affected by the exposure time of polymer to high temperature. These results give better understanding and provide additional knowledge as the conventional research did not fully reveal the efficiency of polymer gel with retarder that was prepared with high salinity for high-temperature application. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.